Cretan Hieroglyphic and Linear A - Tomas, Helena (Array, 2010)
The contribution gives a concise, but full informative overview of two Minoan scripts and administrative systems: Cretan Hieroglyphic and Linear A. It is divided into three sections: 1. Chronology and distribution, 2. Signary, 3. Types of documents.